A Semi-recumbent Eccentric Cycle Ergometer Instrumented to Isolate Lower Limb Muscle Contractions to the Appropriate Phase of the Pedal Cycle - Walsh, Joel A.; McAndrew, Darryl J.; Henness, Douglas J.; Shemmell, Jonathan; Cuicuri, Dominic; Stapley, Paul J. (Frontiers in Physiology, 2021)
Eccentric (ECC) cycling is used in rehabilitation and sports conditioning settings. We present the construction and mode of operation of a custom-built semi-recumbent ECC cycle designed to limit the production of lower limb muscle activity to the phase of the pedal cycle known to produce ECC contractions. A commercially available semi-recumbent frame and seat (Monarch, 837E Semi-recumbent Bike, Sweden) were used to assemble the ergometer. An electrical drive train system was constructed using individual direct drive servo motors. To avoid active muscle activation occurring during the non-ECC pedaling phase of cycling, a ‘trip’ mechanism was integrated into the drivetrain system using a servo-driven regenerative braking mechanism based on the monitoring of the voltage produced over and above a predetermined threshold produced by the motors. The servo-drive internal (DC bus) voltage is recorded and internally monitored during opposing (OPP) and non-opposing (N-OPP) phases of the pedal cycle. To demonstrate that the cycle functions as desired and stops or ‘trips’ when it is supposed to, we present average (of 5 trials) muscle activation patterns of the principal lower limb muscles for regular ECC pedal cycles in comparison to one pedal cycle during which the muscles activated outside the desired phase of the cycle for a sample participant. This semi-recumbent ECC cycle ergometer has the capacity to limit the occurrence of muscle contraction only to the ECC phase of cycling. It can be used to target that mode of muscle contraction more precisely in rehabilitation or training studies